Design and implementation of an efficient FIR digital filter. Issue 1 (1st January 2017) - Zahoor, Sumbal; Naseem, Shahzad
Abstract: Digital signal processing (DSP) circuits are extremely important in computing and communications areas. One application of DSP is a Finite impulse response (FIR) filter. The principle objective of this exploration is to present a methodology for an upgraded framework of a FIR digital filter from software level to the hardware level. It includes the selection of design method, structure and cost effective hardware utilization. Theoretical and experimental results performed FIR band pass filter suggests that the window design method is relatively simple and easy to use because of the availability of well-defined equation. Comparison presented that Kaiser window gives the minimum main-lobe width and a sharp cut-off which means this window has less transition width and the study showed that the Direct-Form structure approach is simpler and offers a better performance than other common filter structures. It results in low cost, reduced area and more robust to withstand the quantization errors. For efficient hardware realization, the paper investigates the impacts of quantization on frequency response by progressively diminishing the quantity of bits in every coefficient using an iterative algorithm to a level where its frequency response matches to the novel requirements. Experimental study of coefficient quantization uncovers a connection between the quantity of bits, number of coefficients and the frequency response that consequence in reduced area and better speed. The synthesis results show that the discussed technique can substantial help in lessening the equipment assets. Computer aided design (CAD) tools are used to implement the design by adopting the behavioural level design method.